(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article discusses pneumonia in children and the diagnostic methods used to detect it. It covers the clinical signs, laboratory and instrumental methods of investigation, and modern medical diagnostic approaches. It also analyzes age-specific symptoms and diagnostic algorithms. This article is useful for pediatricians, medical students, nurses, and parents.